Anthocyanin-Rich Extract from Purple Sweet Potatoes Modified Body Weight, Visceral Fat and Circulatory IL-10 in Stressed-Mice - Kurnianingsih, Nia; Rahma, Oktivani Adelathifa; Prayogo, Nabila Putri; Rayhanna, Qanitha Ailsya; Fahanani, Agwin Fahmi; Suprapto, Ratih Paramita; Prakosa, Ardani Galih; Ratnawati, Retty (Pharmaceutical Sciences and Research, 2024)
Stress-induced inflammation and oxidative stress mechanisms thus plant bioactive compounds as anti-inflammation and antioxidants are placed as novel strategies to resist the adverse effects of stress. Purple sweet potatoes (PSP) as a rich source of macronutrients and anthocyanin showed health benefits as neuroprotective and metabolic diseases. However, limited research explored the effect of PSP extract on stressed animal models. This study aimed to evaluate the bioactive compound analysis of PSP and the effect on body weight gain (BW), visceral fat (VF), and interleukin-10 (IL-10) of stressed model mice. Adult male BALB/c mice (6-8 weeks) were divided into control (CTRL), and stress (STR), stress+anthocyanin-rich extract (ANC) of PSP dose 10, 20, and 40 mg/kgBW. Stress was exposed as restraint stress for 2 hours/day for 14 days. The ANC was administered once a day orally. The IL-10 was measured by enzyme-linked immunosorbent assay (ELISA). Qualitative plant compound analysis showed the presence of flavonoids, alkaloids, phenolics, glycosides, and tannins in PSP extract. The PSP extract also contains a high level of total anthocyanin, 2468.9 ± 159.38 mg/l, and high antioxidant activity. This study observed tendencies to decrease BW and VF following ANC dose of 10 mg/kgBW treatment. The administration of ANC significantly increased the level of circulatory IL-10 cytokine. In conclusion, an anthocyanin-rich extract of PSP modified BW, VF, and IL-10 levels of restraint-stressed model mice.